The glycophospholipid-linked folate receptor internalizes folate without entering the clathrin-coated pit endocytic pathway (The Rockefeller University Press, 1990)
The folate receptor, also known as the membrane folate-binding protein, is maximally expressed on the surface of folate-depleted tissue culture cells and mediates the high affinity accumulation of 5- methyltetrahydrofolic acid in the cytoplasm of these cells. Recent evidence suggests that this receptor recycles during folate internalization and that it is anchored in the membrane by a glycosyl- phosphatidylinositol linkage. Using quantitative immunocytochemistry, we now show that (a) this receptor is highly clustered on the cell surface; (b) these clusters are preferentially associated with uncoated membrane invaginations rather than clathrin-coated pits; and (c) the receptor is not present in endosomes or lysosomes. This receptor appears to physically move in and out of the cell using a novel uncoated pit pathway that does not merge with the clathrin-coated pit endocytic machinery.